Hyers-Ulam Stability of Linear and Nonlinear Differential Equations of Second Order - Qarawani, Maher Nazmi (International Journal of Applied Mathematical Research, 2012)
In this paper we established the Hyers-Ulam stability of a nonlinear differential equation of second order with initial condition. We also proved the Hyers -Ulam stability of a linear differential equation of second order with initial condition.